A Primer on Psychotherapy Process Research: A Review of Cognitive Therapy of Depression. (December 2015) - Pfeifer, Benjamin J; Strunk, Daniel R
Abstract : Researchers conducting psychotherapy process research aim to understand the process by which efficacious psychotherapies achieve therapeutic benefits. A key challenge in this research is how to maximise what can be learned from naturalistic longitudinal data. We provide a selective overview of research examining the process of change in cognitive therapy of depression. While the efficacy of this treatment is widely recognised, a consensus regarding how the treatment reduces depressive symptoms and provides protection from relapse and recurrence has yet to be reached. We review the current state of the research addressing the process of change in cognitive therapy, highlighting how specific methodological features can be used to better understand the process by which this treatment achieves its effects. We highlight the importance of two key challenges to making causal inferences from a process–outcome relation: (a) establishing the temporal precedence of predictors to outcome variables, and (b) evaluating whether any relations identified could be spurious. We argue that methodologically rigorous studies tend to support key claims of the model underlying cognitive therapy of depression. We conclude by considering future directions. For example, we highlight the importance of efforts to understand patient characteristics that may moderate process–outcome relations and could ultimately prove useful in tailoring treatment to best suit individual patients.